2012
DOI: 10.1038/ijo.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Physician weight loss advice and patient weight loss behavior change: a literature review and meta-analysis of survey data

Abstract: Primary care providers (PCPs) can empower their patients to make health-promoting behavior changes. Many guidelines recommend that PCPs counsel overweight and obese patients about weight loss, yet few studies examine the impact of provider weight loss counseling on actual changes in patient behavior. We performed a systematic review and meta-analysis of published studies of survey data examining provider weight loss counseling and its association with changes in patient weight loss behavior. We reviewed the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 39 publications
(46 reference statements)
9
155
1
1
Order By: Relevance
“…Nonetheless, physician referral to weight management treatment appeared to increase treatment enrollment compared to families who self-referred, which is also consistent with reports that healthcare provider recommendation to engage in weight loss treatment is associated with greater motivation to participate in treatment 31 and increases the likelihood that patients will engage in health behavior change. 32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, physician referral to weight management treatment appeared to increase treatment enrollment compared to families who self-referred, which is also consistent with reports that healthcare provider recommendation to engage in weight loss treatment is associated with greater motivation to participate in treatment 31 and increases the likelihood that patients will engage in health behavior change. 32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs.…”
Section: Discussionmentioning
confidence: 94%
“…Although the current analysis defined seeking care from a physician for obesity as the final stage of the care cascade, this step may be necessary but not sufficient for adequate diagnosis, counseling, and referral for obesity‐related treatment services. Studies suggest that obesity is underdiagnosed in primary practice and that many patients with obesity may not receive adequate counseling and treatment for weight management 14, 15. Increasing access and use of obesity‐related treatments will likely involve addressing provider beliefs, attitudes, and perceptions toward screening, diagnosis, and treatment of obesity 16.…”
Section: Discussionmentioning
confidence: 99%
“…The act of the PCP referral may have a similar influence as receiving behavioral counseling or may be done in conjunction with behavioral counseling. A recent meta-analysis of physician weight loss advice and patient weight loss attempts demonstrated a significant impact (OR 3.85); the authors also noted that there was a positive association between provider weight loss advice and actual patient weight loss [16]. For HLP participants, we do not know the extent to which physician weight loss advice occurred along with the referral; this represents a potential confounder that could not be addressed in this study.…”
Section: Discussionmentioning
confidence: 55%